Islamic Education in Indonesia and Malaysia: Comparison of Islamic Education Learning Management Implementation - Munastiwi, Erni; Marfuah (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2019)
This study aims to reveal the comparative management of Islamic Education (Islamic Education) learning in Indonesia and Malaysia. The research method was a case study. The aspect of the study includes planning, implementation, and evaluation. Data collecting techniques were documents, archive records, interviews, and observations. The informant selection technique was a purposive sampling procedure from Madrasah Ibtidaiyah (MI) Bego, Sembego, Maguwoharjo, Depok, Sleman, Yogyakarta, Indonesia and Sekolah Rendah Malaysia (Malaysian Primary School) or Sekolah Kebangsaan (Malay-medium National Schools) Jelotong, Paritraja, Batu Pahat, Johor, Malaysia. The results of the study show that both Indonesia and Malaysia produce similarities in terms of the stages of the planning, implementation, and evaluation processes. The uniqueness of other similarities can be found in choosing the topic of Islamic religious subjects in the learning process. In addition to the similarities, there are differences in the underlying philosophy of making an Islamic Education curriculum.